Prevalence of urinary incontinence, its risk factors and effect on the quality of life in women after their first delivery / Bahiyah Abdullah … [et al.] - Abdullah, Bahiyah; Ayub, Siti Hajar; Mohd Zahid, Akmal Zulayla; Abd Rahman, Noorneza; Isa, Mohamad Rodi (Universiti Teknologi MARA Cawangan Selangor, 2017)
Although urinary incontinence is commonly associated with increasing parity, there is however a lack of published data on urinary incontinence among primiparous women. This study aims to determine its prevalence among primiparous women at 6-8 weeks postpartum, its risk factors and effects to their quality of life. Methods: This is a crosssectional study involving primiparous women at 6-8 weeks postpartum. Women in their third trimester were recruited using convenience sampling. Data were obtained using a study proforma, and International Consultation on Incontinence Questionnaire – Short Form (ICIQSF) over a face-to-face interview. The same questionnaire with additional enquiries on delivery was completed over a telephone interview at 6-8 week postpartum. Data were analysed using chi-square and simple logistic regression tests contained in the Statistical Package for Social Science version 20.0. Results: Three hundred and six women participated in this study. The prevalence of urinary incontinence in the third trimester of pregnancy was 34.3% (95%CI: 29.0, 39.7) and dropped to 5.2% (95% CI: 2.7, 7.7) at 6-8 weeks postpartum. Childhood enuresis and postpartum body mass index were the two factors that showed significant association with postpartum urinary incontinence. Urinary incontinence in 95 (31%) women had resolved by 6-8 weeks postpartum, whereas 10 (3.3%) women still had persistent symptom. A small proportion of women (2.0%) developed urinary incontinence in the postpartum period. Majority of women with urinary incontinence did not feel it significantly affected their quality of life. The ICIQ- SF mean score was 6.13 (range 2- 12). Conclusions: Postpartum urinary incontinence is rather uncommon among primiparous women and does not seem to affect their quality of life. Childhood enuresis and postpartum BMI were risk factors associated with postpartum urinary incontinence.